Influence of decreased muscular blood flow induced by external compression on muscle activation and maximal strength after a single bout of low-intensity exercise - Sato, Yoshiaki; Sugaya, Masato; Abe, Takashi; Ozaki, Hayao; Ogasawara, Riki; Sakamaki, Mikako; Yasuda, Tomohiro (Taiikugaku kenkyu, 2011)
It has been reported that low-intensity exercise training with restriction of muscular blood flow (LI-BFR) results in a significant increase of muscle size and strength, although the mechanisms of BFR-induced muscle adaptation are still poorly understood. Changes in muscle activation level during a BFR exercise session may be an important factor for improvement of muscle size and function. However, the relationship between the actual level of induced blood flow restriction and muscle stimulated during the exercise has not yet been explored. The purpose of this study was to investigate the relationship between muscle activation level evaluated by electromyography (EMG) and muscular blood flow or muscle fatigue during low-intensity resistance exercise with and without BFR. Ten young men participated in three experimental trials: exercise without BFR (CON), exercise with moderate external compression (1.4×systolic arterial pressure, BFR-L), and exercise with high external compression (1.8×systolic arterial pressure, BFR-H). Each subject performed low-intensity (20% of one repetition maximum, 1RM) knee extension exercise (30 reps followed by 3 sets of 15 reps, with a 30-s rest between sets). Maximum voluntary isometric strength (MVC) and thigh muscle blood flow were measured before and immediately after each exercise session. Surface EMG was recorded from the quadriceps muscle (vastus lateralis and vastus medialis) during the exercise session, and the integrated EMG (iEMG) was calculated. iEMG increased gradually during each exercise session in all three trials, and the relative increase in iEMG tended to be greater in BFR-H (P=0.07). Decreases in MVC were associated with the magnitude of external compression (CON: −3%, BFR-L: −13%, BFR-H: −25%), and significant differences were found between CON and BFR-L or BFR-H and between BFR-L and BFR-H. Significant positive correlations were observed between changes in MVC and iEMG (r=0.49, P<0.01) and between changes in MVC and muscle blood flow (r=0.56; P<0.01). Our results indicate that BFR-induced increases in muscle activation are correlated with decreased muscle blood flow resulting from external compression and the level of muscle fatigue.